Functional Suitability Testing of Web-Based Warehouse Inventory Application Using Black Box Testing - Sekar Ajeng Kinasih; Reza Sahputra; Chairul Anwar (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
Warehouse inventory management increasingly relies on web-based applications for real-time stock monitoring amidst the complexity of the Indonesian supply chain. This study evaluates the functional suitability of a Web-Based Warehouse Inventory Application using black box testing according to the ISO/IEC 25010 standard. Using a descriptive qualitative approach, the study population includes 11 functional modules, with a purposive sample of 50 test cases that test authentication, master data, transactions, and reports. The instruments consist of structured test cases based on equivalence partitioning, boundary value analysis, decision table testing, and use case testing, analyzed through PASS/FAIL comparisons, defect severity classification according to ISO/IEC 29119, and thematic pattern identification. The results show an 85% success rate for core operations such as login validation, CRUD functions, and stock reporting, but critical failures were found in stock validation (allowing negative stock), dashboard access without login, lack of session timeout, and the transaction edit feature. In conclusion, although the basic functions meet operational needs, security and data integrity gaps require immediate remediation for production readiness.